Proceedings of the Forty-Seventh Annual ACM Symposium on Theory of Computing 2015
DOI: 10.1145/2746539.2746627
|View full text |Cite
|
Sign up to set email alerts
|

Test-and-Set in Optimal Space

Abstract: The test-and-set object is a fundamental synchronization primitive for shared memory systems. This paper addresses the number of registers (supporting atomic reads and writes) required to implement a one-shot test-and-set object in the standard asynchronous shared memory model with n processes. The best lower bound is log n − 1 [12, 21] for obstruction-free and deadlock-free implementations, and recently a deterministic obstruction-free implementation using O( √ n) registers was presented [11]. This paper clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Space Reference Comments strong adaptive unbounded ⌈log n⌉ + 1 [21] deadlock-free only strong adaptive O(1) Θ(1) [22,23] 2-process implementation strong adaptive O(log n) Θ(n) [1] strong adaptive O(log k) Θ(n 3 ) [5] k is the contention r/w-oblivious O(log log n) Θ(n 3 ) [2] location-oblivious O(log * k) Θ(n) Theorem 4r/w-oblivious O(log log k) Θ(n) Theorem 6strong adaptive O(log k) Θ(n) Theorem 7oblivious O(log * k) Θ(log n) [13] uses impl. of Theorem 4 Table 1: Randomized TAS implementations.…”
Section: Adversary Timementioning
confidence: 99%
See 2 more Smart Citations
“…Space Reference Comments strong adaptive unbounded ⌈log n⌉ + 1 [21] deadlock-free only strong adaptive O(1) Θ(1) [22,23] 2-process implementation strong adaptive O(log n) Θ(n) [1] strong adaptive O(log k) Θ(n 3 ) [5] k is the contention r/w-oblivious O(log log n) Θ(n 3 ) [2] location-oblivious O(log * k) Θ(n) Theorem 4r/w-oblivious O(log log k) Θ(n) Theorem 6strong adaptive O(log k) Θ(n) Theorem 7oblivious O(log * k) Θ(log n) [13] uses impl. of Theorem 4 Table 1: Randomized TAS implementations.…”
Section: Adversary Timementioning
confidence: 99%
“…Until recently, it was not unknown whether any randomized wait-free (or obstruction-free) TAS implementation exists that uses fewer than O(n) registers. After completion of the draft of this paper, Giakkoupis, Helmi, Higham, and Woelfel [12,13] presented deterministic obstruction-free algorithms that use only O( √ n) and O(log n) registers, respectively. As the authors observed, these algorithms can be turned into randomize wait-free ones, and can be combined with the first algorithm proposed in this paper to achieve O(log * n) expected max-step complexity in the oblivious adversary model, with O( √ n) and O(log n) space complexity, respectively.…”
Section: Adversary Timementioning
confidence: 99%
See 1 more Smart Citation
“…Another related line of work has focused on the space complexity of this problem, which is now resolved. Specifically, it is known that Ω(log n) distinct registers are necessary [28,16], and a breakthrough result by Giakkoupis, Helmi, Higham, and Woelfel [15] provided the first asymptotically matching upper bound of O(log n), improving upon an O( √ n) algorithm by the same authors [14]. The clear gap in the complexity landscape for this problem concerns time complexity lower bounds.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an O( √ n) deterministic obstruction-free upper bound was given in [GHHW13]. The final breakthrough was the recent obstruction-free algorithm designed by Giakkoupis et al [GHHW14], with O(log n) space complexity, essentially closing the problem 1 . For consensus, an upper bound with n registers was long known from [AH90].…”
Section: Introductionmentioning
confidence: 99%